Specific connections of the interpeduncular subnuclei reveal distinct components of the habenulopeduncular pathway. Issue 12 (30th May 2017) - Quina, Lely A.; Harris, Julie; Zeng, Hongkui; Turner, Eric E.
Abstract: The habenulopeduncular pathway consists of the medial habenula (MHb), its output tract, the fasciculus retroflexus, and its principal target, the interpeduncular nucleus (IP). Several IP subnuclei have been described, but their specific projections and relationship to habenula inputs are not well understood. Here we have used viral, transgenic, and conventional anterograde and retrograde tract‐tracing methods to better define the relationship between the dorsal and ventral MHb, the IP, and the secondary efferent targets of this system. Although prior studies have reported that the IP has ascending projections to ventral forebrain structures, we find that these projections originate almost entirely in the apical subnucleus, which may be more appropriately described as part of the median raphe system. The laterodorsal tegmental nucleus receives inhibitory inputs from the contralateral dorsolateral IP, and mainly excitatory inputs from the ipsilateral rostrolateral IP subnucleus. The midline central gray of the pons and nucleus incertus receive input from the rostral IP, which contains a mix of inhibitory and excitatory neurons, and the dorsomedial IP, which is exclusively inhibitory. The lateral central gray of the pons receives bilateral input from the lateral IP, which in turn receives bilateral input from the dorsal MHb. Taken together with prior studies of IP projections to the raphe, these results form an emerging map of the habenulopeduncular system that has significant implications for the proposed function of the IP in a variety of behaviors, including models of mood disorders and behavioral responses to nicotine. Abstract : The interpeduncular nucleus receives specific inputs from the medial habenula, forming the habenulopeduncular system. Here we show that the subnuclear specificity, lateralization, and neurotransmitter phenotype of the interpeduncular nucleus efferents define specific projections to the raphe and pontine tegmentum with important implications for the function of this pathway